You are on page 1of 7

MATH 1 - College Algebra

Chapter 2: ALGEBRAIC EXPRESSIONS


Jose Arnaldo B. Dris
Department of Mathematics and Physics
Institute of Arts and Sciences
Far Eastern University
josearnaldobdris@gmail.com
January 6, 2016
The field axioms and theorems (i.e., properties of equality of real
numbers) of the previous chapter furnish the basis for the operations
which we shall perform in this chapter. As a preliminary to this study,
we need to introduce certain ideas and definitions.

1.
2.
3.
4.
5.
6.

Fundamental Operations of Algebra


addition
subtraction
multiplication
division
evolution of powers
extraction of roots

Definition 2.1.1 When numbers (i.e. constants) and letters, standing


for numbers (i.e. variables), are combined by applying one or more of
the fundamental operations of algebra, the result is called an ALGEBRAIC EXPRESSION.
An algebraic expression may consist of a plus and/or minus sign as
well as numbers and letters representing numbers. Each of the parts
with the sign preceding it is called a TERM. If the sign of the first term
of an algebraic expression is a plus (+) sign, it may be omitted and is
understood.
Examples:
1. 3a is an expression of one term.
1

2. 2x + 3y is an expression with the terms 2x and 3y.


3. mn pq + 7 is an expression with the terms +mn, pq, and +7.
4. (mn pq) + 7 has two terms, (mn pq) and +7.
Definition 2.1.2
MONOMIAL - expression of one term
BINOMIAL - expression of two terms
TRINOMIAL - expression of three terms
MULTINOMIAL - indicates an expression of two or more terms
The letters in an algebraic expression are called variables (or literal
constants). For example, x and y are variables in the expressions:

and

2 p
+ y1
x
xy +

x1
+ 6.
x+1

Each of two or more numbers which are multiplied together to form


a product is called a FACTOR. In the product 5xy, for example, 5, x,
and y are the factors. A numerical factor, such as the 5, may be called
the COEFFICIENT of the variable factors. More generally, any factor
or factors of the product may be regarded as the coefficient of the other
factors. Thus, in 5xy, 5x is the coefficient of y, x is the coefficient of 5y,
and so on.
Two terms of an algebraic expression that are identical or that differ
only in their numerical coefficients are called LIKE or SIMILAR terms.
Thus, 3x2 y and 2x2 y are like terms, and 2y 2 and 2y are UNLIKE terms.
The same factor often occurs two, three or more times in a product.
A product of this kind may be expressed by writing the factor the total
number of times, but it is more convenient to use a shorthand notation.
Recall: Definition 2.1.3
If a is a real number and n is a positive integer, then
an = a a a a
where there are n factors of a.

The quantity an is called the nth power of a, or a to the nth. The


number a is called the BASE, and n is called the EXPONENT of the
base.
ADDITION OF ALGEBRAIC EXPRESSIONS is achieved by combining like terms. In order to accomplish this addition, the expressions
may be arranged in rows with like terms in the same column; these
columns are then added.
Example 1: Add 7x + 3y 3 4xy, 3x 2y 3 + 7xy, and 2xy 5x 6y 3 .
SOLUTION:
Write
7x

3y 3

3x

2y 3

4xy
7xy

6y 3

5x

2xy

=================================
5y 3

5x

5xy

Hence, the result is 5x 5y 3 + 5xy.


z2

Example 2: Add x2 + y 2 z 2 + 2xy 2y, y 2 + z 2 x2 + 2yz 2xz,


+ x2 y 2 + 2xz 2xy, and 1 x2 y 2 z 2 .
SOLUTION: Arranging:
x2
x2

+ y2
+ y2

x2

y2

x2

z2

+ 2xy

+ z2

+ 2yz

+ z2
y2

2yz

2xy

2xz
+ 2xz

z2

+1

=================================
0+

0+

0+

0+

0+

0+

The result of the addition is 1.


REMOVAL OF GROUPING SYMBOLS is governed by the following laws:

1. If a (+) sign precedes a symbol of grouping, this symbol of grouping may be removed without affecting the terms contained.
2. If a () sign precedes a symbol of grouping, this symbol of grouping may be removed if each sign of the terms contained is changed.
3. If more than one grouping symbol is present, the inner ones are
to be removed first.
With the following equations we illustrate the procedure when introducing parentheses:
3 4x 6y + 7z = 3 (4x + 6y 7z)
x + 2y + z 4 = x (2y z + 4)
a + 3b 3c + 5 = a + (3b 3c + 5)

SUBTRACTION OF TWO ALGEBRAIC EXPRESSIONS is achieved


by changing the sign of every term in the expression which is being subtracted (sometimes called the subtrahend ) and adding this result to the
other expression (called the minuend ).
Example 3: Subtract 2x2 3xy + 5y 2 from 10x2 2xy 3y 2 .
SOLUTION:


 

 

10x2 2xy 3y 2 2x2 3xy + 5y 2 = 10x2 2xy 3y 2 + 2x2 + 3xy 5y 2


= (10x2 2x2 ) + (2xy + 3xy) + (3y 2 5y 2 ) = 8x2 + xy 8y 2

Example 4: Subtract 4xy +ab2 3a2 +2ab from 4x2 y 3ab+2a2 xy.
SOLUTION:


4x2 y 3ab + 2a2 xy 4xy + ab2 3a2 + 2ab

= 4x2 y 3ab + 2a2 xy + 4xy ab2 + 3a2 2ab

= (4x2 y) + (xy 4xy) + (3ab 2ab) + (2a2 + 3a2 ) + (ab2 )


4

= 4x2 y 5xy 5ab + 5a2 ab2

ASSIGNMENT: To be handed in next class meeting.


1. (5 points) Add: a2 ab + 2bc + 3c2 , 2ab + b2 3bc 4c2 ,
ab 4bc + c2 a2 , and a2 + 2c2 + 5bc 2ab.
2. (5 points) Subtract 2s3 +3s2 r2sr2 3r3 from r3 3r2 s+4rs2 s3 .
Definition 2.1.4
A POLYNOMIAL of degree n, n a nonnegative integer, is an algebraic
expression of the form
a0 xn + a1 xn1 + a2 xn2 + . . . + an2 x2 + an1 x + an ,
where each ai is a real number with a0 6= 0.
Examples:
1. 10 - Polynomial of degree 0
2. 3x + 4 - Polynomial of degree 1 (linear)
3. (5/4)x2 x 1 - Polynomial of degree 2 (quadratic)
2
1
4. xx1
2 +1 - NOT a polynomial because it is equal to (x 1)(x + 1)
1
1
2
5. 2x 3x + 5 x - NOT a polynomial because it contains x = x1

6. x + 1 + x 1 3 x2 + x + 1 - NOT a polynomial because it is


equal to
(x + 1)1/2 + (x 1)1/2 (x2 + x + 1)1/3

The following theorem may be established by repeated applications


of the distributive axiom.
THEOREM The product of two polynomials is the sum of all results
obtained by multiplying all of the terms of one polynomial by each term
of the other.
MULTIPLICATION OF ALGEBRAIC EXPRESSIONS
1. To multiply two or more monomials: Use the laws of exponents,
the rules of signs, and the commutative and associative laws of multiplication.

EXAMPLE: Multiply 3x2 y 3 z, 2x4 y, and 4xy 4 z 2 .


Write the product as
(3x2 y 3 z)(2x4 y)(4xy 4 z 2 ).
Rearranging according to the commutative and associative laws,
{(3)(2)(4)}{(x2 )(x4 )(x)}{(y 3 )(y)(y 4 )}{(z)(z 2 )}.
Combining using rules of signs and laws of exponents to obtain
24x7 y 8 z 3 .
The second step may be done mentally when experience is acquired.
2. To multiply a polynomial by a monomial: Multiply each term of
the polynomial by the monomial and combine the results.
EXAMPLE: Multiply 3xy 4x3 + 2xy 2 by 5x2 y 4 .
Write


(5x2 y 4 ) 3xy 4x3 + 2xy 2 = (5x2 y 4 )(3xy)+(5x2 y 4 )(4x3 )+(5x2 y 4 )(2xy 2 )


= 15x3 y 5 20x5 y 4 + 10x3 y 6

3. To multiply a polynomial by a polynomial: Multiply each of the


terms of one polynomial by each of the terms of the other polynomial
and combine results. It is often very useful to arrange the polynomials
according to descending powers of one of the variables involved.
EXAMPLE: Multiply 3x + 9 + x2 by 3 x.
Arranging in descending powers of x:
(x2 3x + 9)(x + 3) = (x)(x2 3x + 9) + (3)(x2 3x + 9)
= (x3 + 3x2 9x) + (3x2 9x + 27) = x3 + 6x2 18x + 27
DIVISION OF ALGEBRAIC EXPRESSIONS
1. To divide a monomial by a monomial: Find the quotient of the
numerical coefficients, find the quotients of the literal factors, and multiply these quotients.

EXAMPLE: Divide 24x4 y 2 z 3 by 3x3 y 4 z.


Write

24x4 y 2 z 3
=
3x3 y 4 z

= (8)(x)

24
3


x4
x3

y2
y4

z3
z

8xz 2
1
2
(z
)
=

y2
y2


2. To divide a polynomial by a polynomial:


(a) Arrange the terms of both polynomials in descending powers of
one of the variables common to both polynomials.
(b) Divide the first term in the dividend by the first term in the
divisor. This gives the first term of the quotient.
(c) Multiply the first term of the quotient by the divisor and subtract
from the dividend, thus obtaining a new dividend.
(d) Use the dividend obtained in (c) to repeat steps (b) and (c) until
a remainder is obtained which is either of degree lower than the degree
of the dividend or of degree zero.
(e) The result is written as follows:
dividend
remainder
= quotient +
.
divisor
divisor